Influence of rainfall on fungal aerobiota in the urban atmosphere over Tianjin, China: A case study. (December 2021) - Niu, Mutong; Hu, Wei; Cheng, Borong; Wu, Libin; Ren, Lujie; Deng, Junjun; Shen, Fangxia; Fu, Pingqing
Abstract: Fungal aerosols, which play significant roles in affecting human health and regional climate, are closely affected by rainfall. But knowledge about the influence of rainfall on fungal aerobiota in the urban atmosphere remains limited. Here, airborne total suspended particles and size-segregated particles were collected from urban Tianjin, China, to investigate such an impact by high-throughput gene sequencing. On non-rainy days, the genera Cladosporium (16.0%), Alternaria (7.9%) and Aspergillus (6.1%) dominated in fungal aerobiota. On rainy days, in addition to Cladosporium (11.1%) and Aspergillus (5.5%), the genus Schizophyllum which is apt to release spores under humid environment became more abundant (8.2%). Airborne fungi were mainly identified as plant endophytes on non-rainy days, while wood saprophytes dominated on rainy days. Precipitation had a significant impact on the fungal aerobiota in small size ranges (<1.1 μm, p < 0.05) and caused an increase in the proportions of the major fungal genera in the particle-size smaller than 1.1 μm (e.g., Cladosporium, Aspergillus and Penicillium ), which may pose more threat to human health. This study provides important insights into precipitation-induced perturbation of fungal aerobiota, especially for those in small size ranges. Moreover, our results revealed the vital role of plants playing in releasing fungi into the air in different pathways on non-rainy and rainy days. Graphical abstract: Image 1 Highlights: The genus Schizophyllum apt to release spores in humid air became more abundant (8.2%) on rainy days. Plants released fungi into the air in different pathways on non-rainy and rainy days. Rainfall had a significant impact on the fungal aerobiota in size smaller than 1.1 μm.